2019
DOI: 10.5195/cajgh.2019.413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight, obesity, and associated risk factors in healthy female adolescents in Tehran, Iran

Abstract: Introduction: Obesity is an important health concern worldwide and is a growing problem in Iran. Adolescent  obesity has a major role in development of adulthood obesity and its complications. The present study was conducted to evaluate the prevalence of overweight, obesity, and associated risk factors in female adolescents living in Tehran, Iran.Methods: This cross-sectional study was carried out among 2,132 female adolescents aged 14-17 years in Tehran recruited between 2017 and 2018. Weight and height were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In similar studies, the rate of abnormal weight in professional drivers was reported to be almost 50% ( 33 ), 61% ( 34 ), and 56.5% ( 35 ). This difference can be associated with high prevalence of obesity in Iran ( 36 ). Based on recent investigations, the rate of overweight/obesity in Iran was calculated to be almost 60% which is in line with the current study, although our statistics are higher due to specific samples ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies, the rate of abnormal weight in professional drivers was reported to be almost 50% ( 33 ), 61% ( 34 ), and 56.5% ( 35 ). This difference can be associated with high prevalence of obesity in Iran ( 36 ). Based on recent investigations, the rate of overweight/obesity in Iran was calculated to be almost 60% which is in line with the current study, although our statistics are higher due to specific samples ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The review identified a substantial body of literature reporting daily PA or SB measures (183 journal articles). However, reports were concentrated mainly in Iran (68 publications), Turkey (37) and Saudi Arabia (27) with none reporting data from Bahrain, Syria or Yemen. There were a number of large cohort studies associated with these concentrations of reporting (e.g., ATLS: Saudi Arabia (Al-Khobar, Jeddah, Riyadh, Al-Ahsa), Kuwait, Qatar, Iraq, Jordan, Oman; CASPIAN: Iran).…”
Section: Discussionmentioning
confidence: 99%
“…This might be because these two hospitals are located in regions of Tehran where underrepresented minorities and patients with a lower socioeconomic status live. According to existing literature, regions of Tehran with lower socioeconomic status and specifically, the districts where these hospitals are located have higher prevalence rates of overweight BMI and obesity ( 33 , 34 ). Consistent with our finding, many studies have reported a disproportionate rate of burden in socioeconomically-disadvantaged individuals with COVID-19 ( 35 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%